2014
DOI: 10.1097/rct.0b013e3182aac58a
|View full text |Cite
|
Sign up to set email alerts
|

Changes Observed in Multiparametric Prostate Magnetic Resonance Imaging Characteristics Correlate With Histopathological Development of Chronic Granulomatous Prostatitis After Intravesical Bacillus Calmette-Guerin Therapy

Abstract: Administration of Bacillus Calmette-Guerin (BCG) has been shown to cause granulomatous prostatitis, a rare inflammatory process that can be mistaken for prostate cancer (PCa). We present a case of a 78-year-old male on active surveillance (AS) for PCa with a subsequent diagnosis of high-grade urothelial carcinoma. Following intravesical BCG therapy, he developed chronic granulomatous prostatitis (CGP). We present serial MRI and biopsy data demonstrating the time interval between BCG administration and the mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…With the inability to differentiate between granulomatous prostatitis and prostate cancer on transrectal ultrasound [23], speci c characteristics of BCG-induced granulomatous prostatitis on MP-MRI have been proposed recently. In the case patient, an abnormal focus showed low signal in T2-weighted images and an apparent diffusion coe cient in the peripheral zone, which has been reported previously [22,24,25,29,37]. These characteristics could occur because the histology of granulomatous prostatitis includes stromal in ltration of chronic in ammatory cells and extracellular uid surrounding the prostatic cells.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…With the inability to differentiate between granulomatous prostatitis and prostate cancer on transrectal ultrasound [23], speci c characteristics of BCG-induced granulomatous prostatitis on MP-MRI have been proposed recently. In the case patient, an abnormal focus showed low signal in T2-weighted images and an apparent diffusion coe cient in the peripheral zone, which has been reported previously [22,24,25,29,37]. These characteristics could occur because the histology of granulomatous prostatitis includes stromal in ltration of chronic in ammatory cells and extracellular uid surrounding the prostatic cells.…”
Section: Discussionsupporting
confidence: 71%
“…It seems that prostate biopsy should be delayed in these patients while PSA is monitored. However, two patients whose PSA level was elevated after BCG instillations were pathologically diagnosed with both granulomatous prostatitis and prostate cancer [24,25]. In an epidemiological study, concomitant prostate cancer was reported in 35.9% of patients with granulomatous prostatitis [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that prostate biopsy should be delayed in these patients while PSA is monitored. However, two patients whose PSA level was elevated after BCG instillations were pathologically diagnosed with both granulomatous prostatitis and prostate cancer [ 26 , 27 ]. In an epidemiological study, concomitant prostate cancer was reported in 35.9% of patients with granulomatous prostatitis[ 17 ].…”
Section: Discussionmentioning
confidence: 99%